Industrial Revolution as a Narrative About Modernisation of the West: Contribution to the History of Historiographic Culture of Great Britain - Raška, Jakub (Dějiny – teorie – kritika, 2016)
The aim of this study is to present a historiographic paradigm of the industrial revolution which is not viewed as the traditionally understood history of the social impact of market economy and technical innovations, or as the history of various industries. Instead of focusing primarily on the historical phenomenon as such, the author emphasises the language which historiography, in this case naturally mainly the British one, used to present this historical phenomenon. The main goal of this text is a historization of a process which expanded the notion of a revolution so as to include not only political events, but also long-term structural transformation of social and economic relations, and the adoption of this term by historians (whereby the first to use the term in this sense was Arnold Toynbee). The author also analyses the most important relevant historiographic works and maps the discussion of the impact of the industrial revolution. Within this context, the often differing analyses and assessments of the industrial revolution in British historiographic production are seen as various narratives of Western modernisation.